Influence Digitalization Accounting and E-Commerce on Improvement Income SME Entrepreneurship in Palopo City, Indonesia - Nurul Azizah; M. Mutmainna; Indah Pratiwi (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of accounting digitalization and e-commerce on increasing the income of Micro, Small, and Medium Enterprises (MSMEs) in Palopo City. This research is motivated by the low implementation of digital-based financial management and limited marketing reach that affect the increase in MSME income. The study used a quantitative approach with a survey method of 107 MSMEs selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of SPSS version 22, after conducting instrument validity and reliability tests. The results indicate that accounting digitalization and e-commerce, both partially and simultaneously, have a positive and significant effect on increasing the income of MSME entrepreneurs in Palopo City. The e-commerce variable has a more dominant influence than accounting digitalization, while the research model can explain 69.8% of the variation in MSME income increase, with the remainder influenced by other factors outside the research model. The research findings indicate that the implementation of accounting digitalization and e-commerce is an effective strategy for improving financial management efficiency, expanding market reach, and increasing the income and sustainability of MSME businesses in the digital era.